Immunoglobulin Y antibodies against colonization-related genes block the growth and infection of Helicobacter pylori - Shiyuan Deng; Xiaoling Luo; Yunxiao Du; Rania G. Elbaiomy; Weihan He; Rong Guo; Ahmed H. El-Sappah; Xiaohong Jian; Yongmei Xie; Mohammed Bakeer; Mohammed Bakeer; Zaixin Li; et al. (Frontiers in Immunology)
IntroductionImmunoglobulin Y (IgY) has emerged as a promising antibody therapy for the eradication of Helicobacter pylori (H. pylori) independent of antibiotics. However, the roles and differences of IgY antibodies targeting various genes against H. pylori remain unclear.MethodsThe recombinant antigens of five colonization-related genes — FlaA, BabA2, NapA, HpaA, and UreB — are prepared using a prokaryotic expression system and then subject to immunize laying hens for IgY production. Subsequently, their biological activities are evaluated, including blocking bacterial growth, attenuating infection in GES-1 cells, and eradicating H. pylori in gastritis mouse models.ResultsThese IgY antibodies can recognize the full-length antigens of H. pylori and exhibit a direct inhibitory effect on the growth and infection of H. pylori with dose-dependent characteristics. Among these, anti-FlaA IgY shows greater antibacterial activity in inhibiting H. pylori growth and preventing adhesion to GES-1 cells. Oral administration of these IgY antibodies for two weeks (20.0 mg·kg−1·day−1) achieves a 25% to 37.5% eradication rate of H. pylori infection in mice. Interestingly, combination treatment with these IgY antibodies, based on their different roles, enhances antibacterial benefits and significantly promotes the recovery of gastrointestinal function.ConclusionOur results indicate that IgY antibodies against colonization-related genes can directly block the growth and infection of H. pylori, and combination treatment with these antibodies offers more advantages in combating H. pylori.